The Influence of Entrepreneurial Orientation and Innovation on the Performance of MSMEs in Indonesia: A Case Study of Generation Z MSMEs - Balya, Muhammad Rafi Raihan; Yuldinawati, Lia (LP2M IAIN Palopo, 2025)
This study aims to investigate the influence of entrepreneurial orientation and innovation on the performance of Micro, Small, and Medium Enterprises (MSMEs) operated by Generation Z in Indonesia. Using a quantitative approach, data were collected through a structured questionnaire distributed to 400 young MSME owners across various regions. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that entrepreneurial orientation significantly and positively affects both innovation and business performance, while innovation also has a significant positive impact on performance. These results highlight the importance of fostering entrepreneurial behavior and innovation capabilities to enhance the competitiveness of Generation Z entrepreneurs. The study offers practical implications for policymakers, educators, and support institutions to strengthen youth-led MSMEs in the digital economy.